Essential PTC Mathcad Prime 3.0 : a guide for new and current users - Maxfield, Brent (Academic Press, 2013)
Learn how to use PTC Mathcad Prime 3.0, one of the world's leading tools for technical computing, in the context of engineering, science, and math applications. Quickly harness the power of Mathcad to solve simple and complex problems. Essential PTC Mathcad is perfect for college students and first-time users as well as for experienced Mathcad users who are moving to Prime 3.0. The book introduces the most powerful functions and features of the new Prime 3.0 software and teaches how to apply them to create comprehensive calculations for any quantitative subject. Examples from several fields demonstrate the power and utility of Mathcad's tools while also demonstrating how users can effectively incorporate other software, such as Excel spreadsheets. A free 12-month student trial edition of PTC Mathcad Prime 3.0 is available by using the registration code included in the book. Provides more applied examples and problems than previous books on Mathcad Includes thorough discussions of Mathcad tools, such as differential equations, 3D plotting, reading from files and writing to filesEach copy of the book includes a code for students to download PTC Mathcad Prime 3.0 Student Edition, giving the user a full year of use from time of installation.